EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Using EdTech in Response to Climate Emergencies in Pakistan - Hayat, Amal; Mazari, Haani; Aslam, Nawaz (EdTech Hub, 2025)
This policy brief explores how EdTech can support a climate-resilient education system, drawing on insights from stakeholder consultations and EdTech Hub's research on learning continuity in response to climate emergencies following the 2022 Pakistan floods. While recovery efforts often focus on restoring physical infrastructure, we argue that a shift to long-term resilience against climate emergencies can be supported by strategic and contextually relevant use of EdTech. The brief highlights the importance of addressing the evolving needs of learners and teachers across all phases of emergencies through preparedness measures and cross-sectoral collaboration. Keywords: Pakistan floods; climate resilience; EdTech; Education in emergencies; South Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Climate, education, and AI: Challenges and opportunities - Haßler, Björn; Taruza, Takudzwa Charisse (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Climate Risk Index 2025 - Germanwatch (2025)
The Climate Risk Index (CRI) ranks countries by the human and economic toll of extreme weather. The latest edition highlights increasing losses and the urgent need for stronger climate resilience and action.

Budget 2025-26 from a climate lens - Naeem, Zainab (2025)
By any measure, Pakistan’s federal budget for FY2025-26 represents a notable evolution in the country's approach to climate change.For a country that has endured some of the most brutal...

World Bank makes 10-year plan with Pakistan for $20 billion in funding - Greenfield, Charlotte (Reuters, 2025)
Pakistan's prime minister on Wednesday welcomed a first-of-its-kind agreement with the World Bank for a plan to focus $20 billion in lending to the cash-strapped nation over the coming decade on development issues like the impact of climate change as well as boosting private-sector growth.

Education in Conflict and Crisis in 2035: Twelve trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in the increase in global conflict and crises that might occur over the next 10 years. It begins by capturing twelve trends, relating to conflict and crisis, that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Parent and Caregiver Engagement in Kenya: Gaps, opportunities, and emerging questions for future research - Flam, Rebekka; Honda, Delanie; Ramesh Vasudevan, Sharanya; Mbugua, Wanjiku (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Marginalised Learners in Southeast Asia: Perspectives from funders and providers on priorities, design, investment, and scaling considerations - Jayasinghe, Neema; Chrisani, Aprillia; Honda, Delanie; Gunawan, Clarissa Jazzlyne (EdTech Hub, 2025)
This report presents the findings of a landscape analysis of EdTech interventions designed for the Southeast Asian context. The analysis aims to understand the extent to which EdTech providers and funders in Southeast Asia address the needs of marginalised learners through their priorities in design, investment, and scaling decisions. It focuses on initiatives targeting marginalised groups and those with potential to scale. The research for the study included interviews with funders engaged in the Southeast Asian EdTech space to examine their perspective on EdTech’s impact on marginalised learners, the approaches they adopt to support inclusive solutions, and the drivers behind their investment decisions. This builds on EdTech Hub’s research for the ASEAN-UK SAGE programme, particularly on how EdTech could be used to support improvements in foundational literacy and numeracy, out-of-school children and youth, and learners with disabilities, as well as overcoming gender barriers to employment through the use of EdTech solutions. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Note de conseils sur la plateforme numérique - Messa, Angele; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2025)
This document is a guidance note on digital platforms, specifically focusing on e-learning and the use of Opale and Moodle software. It aims to support the implementation of a digital learning platform in Madagascar. The report addresses questions and challenges faced by the Ministry of National Education in developing and deploying digital educational content. It covers various aspects of e-learning, including evaluation methods, content structuring, accessibility, interactivity, and technical requirements. Key topics include different evaluation models, types of e-learning evaluation (formative and summative), guidelines for using Opale, tablet specifications for online learning, ensuring course accessibility, and using Moodle both online and offline. The document also provides a checklist for ensuring quality in e-learning course development and implementation. Keywords: e-learning; Moodle; Opale; digital platform; accessibility; usability; Madagascar Ce document est une note d’orientation sur les plateformes numériques, avec un accent particulier sur l’e-learning et l’utilisation des logiciels Opale et Moodle. Il vise à soutenir la mise en place d’une plateforme d’apprentissage numérique à Madagascar. Le rapport aborde les questions et défis rencontrés par le Ministère de l’Éducation Nationale dans le développement et le déploiement de contenus éducatifs numériques. Il traite de divers aspects de l’e-learning, notamment les méthodes d’évaluation, la structuration des contenus, l’accessibilité, l’interactivité et les exigences techniques. Les principaux sujets incluent les différents modèles d’évaluation, les types d’évaluation en e-learning (formative et sommative), les recommandations pour l’utilisation d’Opale, les spécifications des tablettes pour l’apprentissage en ligne, l’accessibilité des cours et l’utilisation de Moodle en mode en ligne et hors ligne. Le document propose également une liste de contrôle pour garantir la qualité du développement et de la mise en œuvre des cours en e-learning. Mots clés: e-learning; Moodle; Opale; platforme numériques; accessibilité; usabilité; Madagascar An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen